THE REFLECTION ON THE CONCEPT OF UNIVERSALS AND ITS SOCIAL-HISTORICAL VERIFICATION - ІГОР ПАСЬКО (Cхід, 2021)
In this article, the author reviews the concept of singular and general. The analysis focus on the problem of universals during social-historical transformation. The author illustrates the manifestation of universals as a category during the Antiquity and the Modern era. The author argues that the shift in perception of Natural law, making an individual the central unit of analysis, happened during the Modernity. This shift leads to the creation of the concept of the social contract and the development of the idea that the will of individuals within a given society has to be the state's law.